The serological surveillance of several groups of patients using antigens of Encephalitozoon hellem and E. cuniculi antibodies to microsporidia in patients - Kucerová-Pospísilová, Z; Ditrich, O (Folia parasitologica, 1998)
This study was undertaken to attempt to identify correlations between microsporidial seroprevalence data in man, clinical diseases and groups of people at the risk of HIV/AIDS infection. Groups of patients were selected according to the predilection of members of the genus Encephalitozoon for nervous and kidney tissue. Female prostitutes and alcohol and intravenous drug abusers were selected as groups at risk of HIV/AIDS infections. A total of 401 samples of human sera were examined for the presence of antimicrosporidial IgG antibodies by ELISA test with a titre of 600 considered borderline positivity. The highest occurrence of antimicrosporidial antibodies was found in the groups of alcohol abusers (16% from 43 patients), intravenous drug abusers (11% from 9 patients) and prostitutes (10% from 80 women) for E. cuniculi antigen and in the groups of psychiatric patients (14% from 44 patients), malaria patients (11% from 38 patients) and alcohol abusers (7% from 43 patients) for E. hellem antigen. The occurrence of specific antibodies of the six examined diagnostic units (glomerulonephritis chronica, pyelonephritis chronica, schizophrenia, dementia, multiple sclerosis and cerebral stroke) was statistically significant only in patients with pyelonephritis chronica and dementia (p < 0.05). No cases of microsporidial infection were found among the female prostitutes by parasitological examination, although one case of giardiasis was identified. Sera of patients with high anti-E. cuniculi and anti-E. hellem antibodies (titres in ELISA of 600 and above) were confirmed by Western blot using E. cuniculi and E. hellem polypeptides, respectively. These results suggest that the examined patients could show residual antibodies from past or latent infections.
Keywords: elektroforéza v polyakrylamidovém gelu; Antigens, Protozoan; demence; Cercopithecus aethiops; těhotenství; Antibodies, Protozoan; Pyelonephritis; Vero Cells; mužské pohlaví; antigeny protozoální; Sentinel Surveillance; HIV infekce; Mice; Encephalitozoon; western blotting; Blotting, Western; Electrophoresis, Polyacrylamide Gel; ženské pohlaví; ELISA; Microsporidia; zvířata; Humans; pyelonefritida; Pregnancy; Encephalitozoon cuniculi; Dementia; protilátky protozoální; sentinelová surveillance; myši; rizikové faktory; Chlorocebus aethiops; Enzyme-Linked Immunosorbent Assay; Female; HIV Infections; Risk Factors; Vero buňky; lidé; Male; Animals